Delegation to Encourage Communication of Problems - NEWMAN, D. PAUL; NOVOSELOV, KIRILL E. (Journal of Accounting Research, 2009)
ABSTRACT We study a principal's choice to centralize or delegate decisions to an agent when delegation can be used to encourage the agent to communicate potential problems. We find that the principal may choose centralization either to exercise better control over the agent's actions or to provide stronger incentives. Delegation emerges in equilibrium only if the costs of effort to acquire information for both the principal and the agent are sufficiently high. We find that increases in the principal's penalties for an incorrect decision may increase the principal's expected payoff, owing to optimal organizational responses. In addition, catastrophic risk, the risk of incorrectly accepting a defective audit (or product), may be greater under centralization than under delegation. Furthermore, catastrophic risk can be increased by well‐intentioned legislative efforts to decrease such risk by, for example, increasing the agent's penalties for failing to take a corrective action, because the organizational structure may change.